MORPHOLOGICAL RELATIONSHIPS AND CONVERSION FACTORS IN SPINY LOBSTER PANULIRUS POLYPHAGUS (HERBST) FROM THE NORTHWEST COAST OF INDIA - Kagwade, P V (Indian Journal of Fisheries, 2011)
Conversion factors have been determined for 5 sets of variables, namely carapace length and total length, abdominal weight and total weight, total length and total weight, total length and abdominal weight and carapace length and abdominal weight. The relationship between the first 2. sets of variables was found to be linear and the other 3 sets, exponential. Carapace is longer in male than in female. The female has a shorter carapace and hence a longer as well as heavier abdomen, whereas the total weight is more in male than in female.